Two Cases of The Follicular Lymphoma of The Breast: An Exceedingly Rare Presentation. (28th October 2021) - Kumar, V; Sonani, H; Patel, T; Lam, J
Abstract: Introduction/Objective: The primary Non-Hodgkin lymphoma of the breast is a very rare entity, which comprises only less than 0.5% of all breast malignancies. The follicular lymphoma of the breast is still rarer as the most common type is diffuse large B cell lymphoma (DLBCL). We are reporting two cases of follicular lymphoma of the breast. Methods/Case Report: Case 1: A 67-year-old female with a history of low-grade follicular lymphoma of the lacrimal gland and cervical lymph node was presented with 1.7 cm irregular soft tissue mass in the upper inner quadrant of left breast identified on CT scan. Microscopic examination showed diffuse infiltration of medium-sized lymphocytes with focal follicular architecture. These lymphocytes were positive for CD20, CD10, BCL2, BCL6, and Ki67 (10%); while negative for CD5, CD3, cyclin D1, and EBER. These findings are consistent with low-grade follicular lymphoma. Subsequently, a biopsy of the right breast mass revealed similar findings. The patient was followed up with a PET scan every six months and doing well. Case 2: A 52-year-old female with a history of low-grade follicular lymphoma of the right hard/soft palate junction was presented with bilateral breast masses identified on mammography. The biopsy was performed and microscopic examination showed vaguely follicular architecture with small to medium-sized lymphocyte infiltration. The flow cytometric analysis revealed CD10 positive B cell population with kappa light chain restriction. Fluorescence in situ hybridization (FISH) analysis showed 96% of cells with BCL2 and BCL6 rearrangement. These findings were consistent with low-grade follicular lymphoma. The patient was started on chemotherapy with good outcomes. Results (if a Case Study enter NA): N/A Conclusion: By reviewing two cases, we emphasize the rarity of follicular lymphoma in the breast. The most important differential diagnosis is extranodal marginal zone lymphoma and DLBCL. In absence of flow cytometric analysis FISH analysis for BCL-2 rearrangement or other molecular analysis is key to diagnose follicular lymphoma.